EBUS/EUS-guided lymph nodal gadolinium injection and MRI of the chest in diagnosis of abnormal lymphatic drainage. A case series - Poletti, Venerino; Petrarulo, Simone; Giampalma, Emanuela; Ravaglia, Claudia; Piciucchi, Sara (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2025)
Impaired lymphatic circulation in the mediastinum may result from congenital disorders, leakage secondary to trauma, or infiltration by neoplasia. It manifests as chylothorax, plastic bronchitis, and/or alveolar fatty pneumonitis. Lymphography, involving the injection of contrast medium into peripheral lymph nodes, was previously utilised but posed challenges in execution and image interpretation. We describe two patients admitted to our department with relapsing chylothorax and respiratory failure associated with “fatty” pneumonitis and plastic bronchitis. The final diagnosis was confirmed by injecting 2 mL of gadolinium into the mediastinal lymph nodes under endoscopic ultrasonography guidance (EBUS), and magnetic resonance imaging (MRI) visualised its distribution.